(untitled) (Research, Society and Development, 2022)
Objective: To investigate the association between the Sense of Coherence (SOC) of guardians and the severity of carious lesions in pediatric patients. Material and methods: This is an analytical cross-sectional study with a quantitative approach, carried out at the Dentistry School Clinic of the Federal University of Ceará - Campus Sobral, with a sample of 43 patients and their guardians, treated at the Pediatric Dentistry Clinic. The research included a survey of dental records to quantify the dmftindex and a questionnaire on oral health and hygiene, sociodemographic and Sense of Coherence (SOC-13) applied to those responsible. Data were analyzed by Fisher’s exact test (p < 0.05). Results: The DMFT found was 5.21 (SD+-2.19). Of the patients analyzed, 69.8% (n=30) had high caries severity (DMFT ≥ 5), associated with a lower age group (p=0.01). The SOC of those responsible had a median of 37 points, showing a tendency of Strong Sense of Coherence in the studied population. There was no statistically significant association between dental caries severity and caregivers’ SOC (p = 0.09). Conclusion: The guardians’ Sense of Coherence was not associated with the severity of carious lesions in the analyzed patients.